13-6b=3+11b

Simple and best practice solution for 13-6b=3+11b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-6b=3+11b equation:


Simplifying
13 + -6b = 3 + 11b

Solving
13 + -6b = 3 + 11b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-11b' to each side of the equation.
13 + -6b + -11b = 3 + 11b + -11b

Combine like terms: -6b + -11b = -17b
13 + -17b = 3 + 11b + -11b

Combine like terms: 11b + -11b = 0
13 + -17b = 3 + 0
13 + -17b = 3

Add '-13' to each side of the equation.
13 + -13 + -17b = 3 + -13

Combine like terms: 13 + -13 = 0
0 + -17b = 3 + -13
-17b = 3 + -13

Combine like terms: 3 + -13 = -10
-17b = -10

Divide each side by '-17'.
b = 0.5882352941

Simplifying
b = 0.5882352941

See similar equations:

| 9n+18=36 | | (99+x)=(176+y) | | -9(x+3)+3x+6=5x+9 | | 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 | | 116=-4(-4y)-9(2y)+y | | (w*3-9)+(w+4)=(w*3-9)+(w+4) | | 2x+3y=5.13 | | 16+b^2+6b=0 | | 4y^6(y^2+9y+2)= | | 8n^2-3n-16=24 | | -10+3x=-4 | | X+y=y+x+200 | | 57=3v+3 | | 89-116=-4(-4y)-9(2y) | | 4x+6+6x=36 | | x+y+z=2000zxy | | (7x-4x)=y | | -5x-2=-2x-17 | | 0.5(2n-10)=22 | | -4x+5+6x=37 | | 183=3+10x | | 20+x*-4=44 | | 12x-10=8x | | 15n=6+25 | | 15n=6+255 | | 7p-2r-6r-2p= | | 5-7m=5 | | 2(3y+6)=2y+4 | | 6=4(3x+12)+13x | | 17-(2m+7)=5+4m-13 |

Equations solver categories